2015
DOI: 10.1002/elps.201500375
|View full text |Cite
|
Sign up to set email alerts
|

Further exploring the absorption and enterocyte metabolism of quercetin forms in the Caco-2 model using nano-LC-TOF-MS

Abstract: When using the Caco-2 intestinal model, the low uptake, intracellular presence at low levels as well as generation of trace metabolites may limit the analysis of flavonoids. To overcome these limitations, we performed a simple but sensitive methodology based on nano-LC-TOF-MS, using an on-line trapping step. The analytical method was validated for quercetin, quercetin 3-O-glucoside, and quercetin 3-O-glucuronide and the reliability for characterization using lock-mass calibration was also assessed along the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The external standard method was used and a linear regression for the calibration curve was estimated using the area under the curve of protopine against concentration. Repeatability was assayed by three consecutive injections of the methanolic solutions of at three levels three times (intraday repeatability) and five times on two different days (interday repeatability) [ 22 ]. The limit of detection (LOD) and quantification (LOQ) were estimated as protopine concentration giving a signal equal to the blank signal plus three and ten standard deviations of the blanks, respectively [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The external standard method was used and a linear regression for the calibration curve was estimated using the area under the curve of protopine against concentration. Repeatability was assayed by three consecutive injections of the methanolic solutions of at three levels three times (intraday repeatability) and five times on two different days (interday repeatability) [ 22 ]. The limit of detection (LOD) and quantification (LOQ) were estimated as protopine concentration giving a signal equal to the blank signal plus three and ten standard deviations of the blanks, respectively [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this vein, the metabolite quercetin-3-glucuronide ( Figure 1 ) was detected in hepatic and immune cells in the liver and in the intestinal mucosa of hyperlipidemic mice fed with a polyphenol-enriched extract of HS, concomitantly with an improved steatohepatitis [ 21 ]. The permeability of the polyphenolic extracts in Caco-2 intestinal human cells, a model of human intestinal absorption, has also been reported [ 50 , 62 ]. The data from these studies revealed a low level of permeability of the complex polyphenolic mixture through the gut barrier, suggesting that the presence of high concentrations of several polyphenols in the extract could lead to a saturation of the specific transport mechanism.…”
Section: Bioavailability Tissue Distribution and Cellular Metabolmentioning
confidence: 99%
“…Finally, an investigation of plant extract or pure polyphenol administration route, body distribution, bioavailability, pharmacokinetics, and synergistic effects with conventional antimicrobials in vivo is necessary. When orally administering the C. salviifolius extract, punicalagins will be poorly bioavailable, and quercetin, upon absorption, will be subjected to different types of metabolism with quercetin-3-O-β-D-glucuronide and quercetin aglycone as the main pharmacologically active metabolites in plasma, in a similar fashion to pure quercetin oral administration [74,75].…”
Section: Discussionmentioning
confidence: 99%